Thirty‐six‐month results of laparoscopic‐based renal denervation plus unilateral laparoscopic adrenalectomy for the treatment of patients with resistant hypertension caused by unilateral aldosterone‐producing adenoma. Issue 5 (16th February 2021) - Liu, Yahui; Zhu, Binbin; Zhu, Lijie; Zhao, Linwei; Fan, Zhiqiang; Ding, Degang; Liu, Zhonghua; Zhao, Qiuping; Qi, Datun; Zhang, You; Wang, Ji‐Guang; Gao, Chuanyu
Abstract: The aim of this study was to explore the long‐term clinical results of Renal denervation (RDN) from the adventitia of the renal artery plus unilateral laparoscopic adrenalectomy to treat patients with resistant hypertension caused by unilateral aldosterone‐producing adenoma (APA). Sixty patients with resistant hypertension caused by APA who were treated at Henan Provincial People's Hospital from December 2016 to March 2018 were selected and randomly assigned to undergo RDN from the adventitia of the renal artery plus adrenalectomy (RDN group, n  = 30) or adrenalectomy alone (control group, n  = 30). Office blood pressure (BP), antihypertensive medication usage and other laboratory characteristics were followed every 6 months through 36 months. Follow‐up data were available at 36 months for 23 of 30 subjects in the RDN group and for 21 of 30 subjects who were in the control group. At 36 months postprocedure, the reduction in the RDN group was 42.2 ± 21.6 mmHg and that in the control group was 29.8 ± 13.5 mmHg ( p  = .029 between the groups). During the follow‐up to 36 months postprocedure, no patients in either the RDN group or the control group died due to surgical complications, and the RDN group had no procedural complications, including renal artery dissection, perforation, and renal artery stenosis. There was no change in the mean eGFR of the two groups, and no serious adverse events were reported. In conclusion, RDN from the adventitia of the renal artery plus unilateral laparoscopic adrenalectomy resulted in sustained lowering of BP at 3 years in a selected population of subjects with resistant hypertension caused by unilateral APA without serious safety concerns.